Tech knowledge: introducing computers for coordinated care. - McCoy, H. Virginia; Vila, Christie Kibort (Health & Social Work, 2002)
The writers describe a three-year intervention project that introduces and supports social work referral technology in three inner-city health service sites. One of the main goals of the intervention project was to expand and standardize the referral capacity of health and social work workers through the introduction of technology. The intervention promoted the use of software specifically designed as an information and referral system, IRis®.